Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

...maps:

$-1 \mapsto i,$

$\infty \mapsto 1,$

$i \mapsto 1+i$

This is driving me mad! Should be easy but I keep getting tied up in knots. Any help much appreciated!

share|improve this question

3 Answers 3

up vote 3 down vote accepted

Suppose the Möbius transformation is that $M(z)=\frac{z+a}{z+b}$, and then by $M(-1)=i,M(i)=1+i$, we can get that $a=2+i,b=2-i$, so the desired Möbius transformation is that $$M(z)=\frac{z+2+i}{z+2-i}.$$

share|improve this answer
1  
It might be worth saying that the form of $M(z)$ you assume comes from the fact that $M(\infty) = 1$. –  t.b. Apr 9 '12 at 15:50
    
Thanks! I hadn't thought of simplifying the original form by dividing the top and bottom by the coefficient of $z$. Lesson learned. –  ABB Apr 9 '12 at 16:04
    
yes, $M(\infity)=1$ is very important! –  Riemann Apr 9 '12 at 16:07

$$f(z)=\frac{az+b}{cz+d}$$ $$f(\infty)=\frac{a}{c}=1$$ $$f(-1)=\frac{-a+b}{-c+d}=i$$ $$f(i)=\frac{ai+b}{ci+d}=1+i$$ We have got four variables, three equations, all you have to do is to solve them, you will can choose one variable freely

share|improve this answer

We can find $\omega(z)=\dfrac{az+b}{cz+d}$ using formula $$\frac{z-z_1}{z-z_2}:\frac{z_3-z_1}{z_3-z_2}=\frac{\omega-\omega_1}{\omega-\omega_2}:\frac{\omega_3-\omega_1}{\omega_3-\omega_2}$$ where $(z_1,z_2,z_3)=(-1,\infty,i)$ and $(\omega_1,\omega_2,\omega_3)=(i,1,1+i).$

In our case we have $$\frac{z+1}{1}:\frac{i+1}{1}=\frac{\omega-i}{\omega-1}:\frac{1}{i},$$ where we change $z-z_2$ with $1$ because $z_2=\infty,$ etc.

And now we find that $\omega=\omega(z)=\dfrac{z+2+i}{z+2-i},$ like previous solutions.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.